FIBTEM clot firmness parameters correlate well with the fibrinogen concentration measured by the Clauss assay in patients and healthy subjects. (2nd November 2020) - de Vries, Judith J.; Veen, Caroline S. B.; Snoek, Charlotte J. M.; Kruip, Marieke J. H. A.; de Maat, Moniek P. M.
Abstract: The Clauss assay is the assay most often used for measuring plasma fibrinogen levels. However, the FIBTEM-assay, determined using thromboelastometry (ROTEM) can also be used to estimate fibrinogen levels. A major advantage of the FIBTEM is that it can provide information about fibrinogen levels within minutes, while the Clauss assay needs 30–60 min before the result is available. The aim of this study was to investigate the correlation between fibrinogen levels measured by the Clauss assay and results from the FIBTEM-assay. We included 111 patients ≥18 years for whom both ROTEM analyses and a fibrinogen measurement using the Clauss assay were available. In addition, ROTEM and Clauss measurements from 75 healthy subjects were included. Spearman correlation was used to determine the association between the results of both assays. The patients included were mostly patients with major trauma or undergoing large surgery (e.g. cardiac surgery or liver transplantation). Strong correlations were found between FIBTEM clot firmness parameters and fibrinogen levels measured by the Clauss assay in patients (Spearman's correlation coefficients (rs ) above 0.80 ( p < .001) for all subgroups) and healthy subjects (rs = 0.66, p < .001). The correlation between early FIBTEM parameters (clot firmness at 5 or 10 min) and the maximum clot firmness was almost perfect (rs above 0.96). Also, the correlation between the α-angle and FIBTEM parameters was strong (rs above 0.7). In conclusion, strong correlations were found between early FIBTEM parameters and fibrinogen levels.